UV-Excited Fluorescence as a Basis for the In-Situ Identification of Natural Binders in Historical Painting: A Critical Study on Model Samples - Margherita Longoni; Ester Sara Cacciola; Silvia Bruni (Chemosensors, 2022)
The fluorescence emission by aged organic binders used in painting is a well-known phenomenon. Several literature studies were devoted to its investigation, both on pure binders and on their mixtures with some pigments. Nevertheless, a systematic study about the real possibility of exploiting such a phenomenon for the non-invasive identification of binders in ancient paintings is still lacking. In the present work, a prototype portable fluorimeter was used to analyze a significant number of model painting samples containing different binders (drying oils, egg yolk, milk, animal glue, and gum Arabic) mixed with various pigments having different hues. The model samples were naturally aged in a period ranging from fifteen to one year. The effects on the spectral pattern due to the different binders, the recipes used to prepare them, and the pigments mixed with them were examined. The fluorescence spectra were corrected for the absorption of the emitted radiation due to the pigments. Finally, the corrected spectra were treated by principal component analysis to determine if the possibility of distinguishing at least the most fluorescent and common binders, i.e., drying oils and egg, existed. It was shown that, even if the technique cannot be effectively applied in the case of mixed or superimposed binders, it allows to put forward at least a preliminary hypothesis when pure binders are used.